Reflexologia sociética e psiclogia histórico-cultural: uma análise das interlocuções entre o pensamento de Vigotski e o Pavlovianismo - Eustaquio Jose de Souza Junior (2008)
The main objective of the present study is to establish possible approximate and distant points among Lev Vigotski Cultural-Historical Theory and one of its most prominent contemporary intellectual known as Soviet Reflexology. To achieve this aim a bibliographic review was perceived with the purpose of giving more visibility to Vigotski intellectual and political paths and of three Soviet Reflexology leading proponents: Ivan Séchenov, Vladimir Bechterew and Ivan Pavlov. Some philosophic, scientific and ideological conditionings of intellectual production from both thinking schools were analyzed considering grant gathering for the beginning of the investigation subsequent phase. Such phase consisted of quantitative and qualitative content analyses of reference made to Soviet Reflexology authors in texts present at Lev Vigotski Selected Works publishing. It was possible to conclude that Soviet Reflexology shows relevant presence in collected texts on Vigotski Selected Works. It was also noticed that there are relevant qualitative changes in Vigotski regards to reflexologists although the critical content related to reflexological denial attribution of scientific statute to conscience study consisted in constant position in the texts analyzed in this work. Moreover, it was confirmed that Vigotski references to reflexologists show fundamental trait in cultural-historical theoretic conjectures, considering that reflexologists presence is one of the most significant among others present in the selection which was the object of this analyses. It was verified that Vigotski seemed to agree with the reflexological statement that reflex learning consists in cognitive development basis, though it emphasizes that in case of human development, verbal signs usage is predominant in cognitive processes build up if compared to more elementary learning and not mediated by culture, which are typical in reflex responses conditioning described by reflexologists.